Competence, opportunity, negotiation and the reconstruction of a professional identity by foreign-trained teachers in Canada. - Xu, Fengying. (University of Ottawa (Canada), 1999)
This study is a three-year longitudinal research project on the linguistic, pedagogical, cultural, emotional and career needs and adjustments of seven foreign-trained teachers who struggled to reconstruct professional identities as teachers in Ontario schools after they had received additional training and qualifications as required by Canadian standards and had become Ontario certified teachers. A co-constructive perspective on identity formation was employed, which allowed data collection by various methods such as analysis of written materials, individual interviews, and group discussions. The research data strongly suggest that these teachers' professional identity in Ontario schools should be understood as a site of joint collaboration between them and significant others in their environment. Due to their culturally and racially different backgrounds from those of the mainstream teachers, these teachers were often placed in a position of having to manage their differences in accents, acts and appearance. This difference-managing process reflected the fact that their professional identity was also ethnically and linguistically defined. Furthermore, given that they were subject to constant subjective outside evaluations of their competencies at a variety of school sites which could not be defined at static points, their professional identities are interpreted as conflictually multiple and constantly changing. The researcher concludes that it is possible for foreign-trained teachers to be accepted within a school system and to be symbolically visible in some positions in schools, but it is very unlikely for them to be visible in classrooms, teaching. The progress of their integration into a school system is effectively impeded by various barriers which reflect just some of today's social ills. Drawing insights from the notion of co-construction of a given identity (Ochs 1993; He 1995), the analysis of opportunity and social identity (Peirce 1994), and the concept of negotiation and professional identity (Thiessen, Bascia & Goodson 1996) in relation to the seven foreign-trained teachers' experiences in Ontario schools, the researcher recommends that serious research attention should be given to the opportunity structure in North America, which, according to Cherryholme's (1988) description of power operations, should be destructured.
Keywords: Education, Bilingual and Multicultural.